Peningkatan Literasi Keuangan sebagai Upaya Membangun Generasi SMK Cerdas Berinvestasi di Era Digital - Laeli Budiarti; Raden Putri Shania Cabysha Melcarina; Arifah Nur Inayah; Syaamil Amanulloh (STAI Darul Qalam Tangerang, 2026)
Advances in digital technology have made it easier to access various financial services, such as mobile banking, digital wallets, and app based investments. However, this ease of access is not always matched by adequate financial literacy, particularly among students. Therefore, this community service activity aims to improve financial literacy and investment awareness about investing among students at SMK Negeri 1 Purwokerto. The activity was conducted using a participatory-educational approach through outreach and interactive discussions, employing a one-group pre-test and post-test evaluation model. The program is held on January 23, 2026, involving 61 students as participants. The material covered included an introduction to financial literacy, personal financial management, investment concepts, as well as the identification of illegal investments and risks associated with digital financial services. The results of the activity showed an increase in participants’ understanding, as demonstrated by a comparison of pre-test and post-test scores. The average score of participants increased from 76.41 to 97.46, or approximately 27.5% after the activity. These results indicate that financial literacy education is effective in improving students’ understanding of financial management and investment in the digital age.